Allelopathic Potential of Rapeseed Cultivars on Germination and Seedling Growth of Weeds - Uremis, I.; Arslan, M.; Sangun, M.K.; Uygur, V.; Isler, N. (Asian Journal of Chemistry, 2010)
Allelopathic suppression of weeds is receiving greater attention as a possible alternative for weed management. Rapeseed (Brassica napus L., var. oleifera) contains allelochemicals that inhibits germination and growth of weed species. Allelopathic potential of 25 rapeseed cultivars on the seed germination, shoot and root growth of Amaranthus retroflexus L. (redroot pigweed), Solanum nigrum L. (black nightshade), Portulaca oleracea L. (common purslane), Physalis angulata L. (cutleaf ground cherry) and Echinochloa colonum (L.) Link. (junglerice) were investigated with shoot and root extracts. All rapeseed cultivars examined inhibited seed germination, shoot and root growth of tested weed species. However, inhibition rates significantly varied among rapeseed cultivars. Significant reductions in seed germination, shoot and root growths were observed as the extract concentration increased. Extracts from both above and below ground parts of rapeseed had inhibitory effect on the tested weed species, but shoot extracts had slightly higher inhibition rates than that of root extracts. Root exudates had also inhibited germination of the tested weed species, but inhibitory effects are not as high as shoot and root extracts. Relative to the germination inhibition of weed seeds, the rapeseed cultivars were categorized as having highly, moderately and low allelopathic potential. Cultivar Westar was found to be highly allelopathic while cultivars Jumbuck, Tobin, Lisoune and Galant were found to be less allelopathic on the tested weed species. Rapeseed cultivars differed in isothiocyanate benzyl and isothiocyanate allyl. Cultivars containing higher level of isothiocyanate benzyl and isothiocyanate allyl had stronger allelopathic capacity. The result of this study showed that a great deal of success could be obtained by incorporation of highly allelopathic rapeseed cultivars into crop rotations to control weeds.